Carbapenem resistant Pseudomonas aeruginosa and Acinetobacter baumannii at Mulago Hospital in Kampala, Uganda (2007–2009) - Kateete, David P. (Springerplus, 2016)
BACKGROUND: Multidrug resistant Pseudomonas aeruginosa and Acinetobacter baumannii are common causes of health care associated infections worldwide. Carbapenems are effective against infections caused by multidrug resistant Gram-negative bacteria including Pseudomonas and Acinetobacter species. However, their use is threatened by the emergence of carbapenemase-producing strains. The aim of this study was to determine the prevalence of carbapenem-resistant P. aeruginosa and A. baumannii at Mulago Hospital in Kampala Uganda, and to establish whether the hospital environment harbors carbapenem-resistant Gram-negative rods. RESULTS: Between February 2007 and September 2009, a total of 869 clinical specimens were processed for culture and sensitivity testing yielding 42 (5 %) P. aeruginosa and 29 (3 %) A. baumannii isolates, of which 24 % (10/42) P. aeruginosa and 31 % (9/29) A. baumannii were carbapenem-resistant. Additionally, 80 samples from the hospital environment were randomly collected and similarly processed yielding 58 % (46/80) P. aeruginosa and 14 % (11/80) A. baumannii, of which 33 % (15/46) P. aeruginosa and 55 % (6/11) A. baumannii were carbapenem-resistant. The total number of isolates studied was 128. Carbapenemase genes detected were bla(IMP)-like (36 %, 9/25), bla(VIM)-like (32 %, 8/25), bla(SPM)-like (16 %, 4/25); bla(NDM-1)-like (4 %, 1/25) in carbapenem-resistant P. aeruginosa, and bla(OXA-23)-like (60 %, 9/15), bla(OXA-24)-like (7 %, 1/15), bla(OXA-58)-like (13 %, 2/15), and bla(VIM)-like (13 %, 2/15) in carbapenem-resistant A. baumannii. Furthermore, class 1 integrons were detected in 38 % (48/128) of P. aeruginosa and Acinetobacter, 37 % (26/71) of which were in clinical isolates and 39 % (22/57) in environment isolates. Gene cassettes were found in 25 % (12/48) of integron-positive isolates. These were aminoglycoside adenylyltransferase ant(4′)-IIb (3 isolates); trimethoprim-resistant dihydrofolate reductase dfrA (2 isolates); adenyltransferase aadAB (3 isolates); QacE delta1 multidrug exporter (2 isolates); quinolone resistance pentapeptide repeat protein qnr (1 isolate); and metallo-β-lactamase genes bla(VIM-4)-like, bla(IMP-19)-like, and bla(IMP-26)-like (1 isolate each). Gene cassettes were missing in 75 % (36/48) of the integron-positive isolates. CONCLUSIONS: The prevalence of carbapenem-resistant P. aeruginosa and Acinetobacter among hospitalized patients at Mulago Hospital is low compared to rates from South-East Asia. However, it is high among isolates and in the environment, which is of concern given that the hospital environment is a potential source of infection for hospitalized patients and health care workers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-016-2986-7) contains supplementary material, which is available to authorized users.